Feasibility and Performance of Hemoglobin A1C Self-Testing During COVID-19 Among African Americans With Type 2 Diabetes. Issue 4 (August 2022) - Woo, Jihun; Whyne, Erum Z.; Wright, Jaylen I.; Lehrer, H. Matthew; Alhalimi, Taha A.; Wang, Tianyu; Saba, Victoria C.; Dubois, Susan K.; Tanaka, Hirofumi; Brown, Sharon A.; Steinhardt, Mary A.
Purpose: The purpose of the study was to determine the feasibility of implementing A1C self-testing at home using the A1CNow® Self Check and to compare the accuracy of the A1CNow to a reference standard in African Americans with type 2 diabetes (T2D). Methods: African American adults with T2D were recruited from 13 different churches (N = 123). Phase 1, conducted during the early phase of the COVID-19 pandemic, examined the feasibility of A1C assessment using the A1CNow performed at home by untrained participants. Phase 2, conducted when in-person research resumed, compared A1C values concurrently measured using the A1CNow and the DCA Vantage™ Analyzer (reference standard) collected by research staff at church testing sites. Results: In Phase 1, 98.8% of participants successfully completed at least 1 at-home A1C test; the overall failure rate was 24.7%. In Phase 2, the failure rate of staff-performed A1CNow testing was 4.4%. The Bland-Altman plot reveals that A1CNow values were 0.68% lower than DCA values, and the mean differences (A1CNow minus DCA) ranged from −2.6% to 1.2% with a limit of agreement between −1.9% to 0.5%. Conclusions: A1C self-testing is feasible for use in community settings involving African American adults with T2D. The A1CNow Self-Check underestimated A1C values when compared with the reference standard. Ongoing improvements in point-of-care devices have the potential to expand research and clinical care, especially in underserved communities.